Department of Accounting, College of Administrative and Financial Sciences, Imam Ja’afar Al-Sadiq University, Baghdad, Iraq. - Saber Abood , Mseer (South Asian Journal of Social Sciences and Humanities, 2025)
This research seeks to clarify the concept of institutional corruption, which many countries suffer from, especially various developing countries, including Iraq. It takes on multiple, broad dimensions, intertwined with various factors, including the effectiveness of external audit and inspection bodies. Therefore, the importance of the research lies in clarifying the role that external audit and inspection bodies can play in eliminating institutional corruption within the government institutions subject to their oversight, and the extent to which these bodies adhere to regulations and laws to preserve public funds. The research yielded a set of conclusions, the most important of which is that there is a clear role for external audit and inspection bodies in identifying cases of institutional corruption in Iraq, but they do not report them to the relevant anti-corruption bodies in a timely manner. Nevertheless, their absence from performing their duties will lead to increased manipulation of public funds, violations and breaches of financial laws, an increase in embezzlement, waste of public funds, and the exploitation of influence and government positions. The research reached a set of recommendations, including the need for serious work by all official and popular sectors to lift all covers on corruption, especially technical covers. Legal and administrative measures are needed to enable external audit and inspection bodies to combat corruption more effectively. Proposals for draft laws criminalizing practices and actions that contribute to the emergence and spread of corruption are also proposed, and legislative bodies are required to approve and implement them. Managements of state institutions are selected from those with a good reputation and professional competence, not based on criteria of proximity or distance from influential authorities